Rheumatoid Arthritis-The Condition and its Management (Homoeopathy for All, 2021)
Rheumatoid arthritis (RA) is a common form of inflammatory arthritis, occurring throughout the world and in all ethnic groups. It is a chronic disease characterized by a clinical course of exacerbations and remissions.1 A chronic multi system disease of unknown etiology characterized by persistent inflammatory synovitis, usually involving peripheral joints symmetrically. Although cartilaginous destruction, bony erosions, and joint deformity are hallmarks, the course of RA can be quite variable. An association with HLA-DR4 has been noted; both genetic and environmental factors may play a role in initiating disease. The propagation of RA is an immunologically mediated event in which joint injury occurs from synovial hyperplasia; lymphocytic infiltration of synovium; and local production of cytokines and chemokines by activated lymphocytes, macrophages,and fibroblasts.2
Keywords: Rheumatoid arthritis; hallmarks; lymphocytic; Rheumatoid arthritis treatment| Homeopathic remedies for Rheumatoid arthritisI Joint pains I Wrist pain